An empirical test on liquidity determinants at microstructure level in Viet Nam - Nguyen, Thi Khanh Linh (H. : ĐHQGHN, 2020)
Using descriptive statistical, correlation matrix, linear regression and logistic regression, the study has determined that the Conventional Liquidity Ratio is the most appropriate methods to measure liquidity in Vietnam stock market.